Dreams and Dust: George R. R. Martin Critiques the White Savior. Issue 2 (1st July 2022) - Young, Joseph Rex
Abstract : An emerging body of opinion cites the Daenerys subplot in George R. R. Martin's A Song of Ice and Fire (1996–) as a white savior narrative. This article argues against this. Martin presents his emblematic medievalist Occident as equally barbaric as his Orient, disabling the Manichean colonialist allegory some scholars perceive in his work. Although Daenerys certainly thinks like a colonialist savior, such discourse makes most sense as Bakhtinian image of a language, exhibited by Martin in concert with depictions of the intractable problems her actions cause, to mount a polemic authorial critique of colonialist literature. Support for this reading can be found elsewhere in Martin's work, in which he frequently critiques uncritical espousals of literary tropes, and in his careful moral variegation of the peoples Daenerys conquers.